PERFORMANCE CHARACTERISTICS OF FABRICS - Daminova Rano Basitovna; Mukhitdinova Nodira (Web of Journals Publishing, 2025)
Optical properties of materials: shine, color, transparency are important performance characteristics. These indicators are taken into account when choosing a model, cutting, sewing products, the nature and pattern of the fabric.
Keywords: Color model, drawing, transparency, color, optical properties.